The Global Digital Compact. - Cerf, Vinton G. (Communications of the ACM, 2024)
This article provides an overview of the need for improvement in all areas of software development with an emphasis on the United Nation's Global Digital Compact, a framework to deal with challenges and opportunities in software and digital technology. Topics include the CrowdStrike software bug, the Internet Governance Forum, and the emphasis of accountability of software developers.